OVERVIEW OF EDUCATIONAL VIDEO MEDIA REGARDING THE ASSESSMENT OF THE JKN MOBILE APPLICATION FOR PATIENTS AT THE KAMARANG COMMUNITY HEALTH CENTER CIREBON REGENCY IN 2025 - Gita Fitri Rahayu; Bhakti Aryani; Bambang Karmanto; Fitria Dewi Rahmawati (Lafadz Jaya Publisher, 2026)
The low utilization of the Mobile JKN application at Kamarang Community Health Center (10.8% in Q3 2025) reflects the digital literacy gap despite the BPJS Kesehatan target. This study aims to develop and evaluate educational video media for Mobile JKN usage. Using a modified ADDIE R&D with a quantitative descriptive approach, 89 JKN patients were purposively selected from a population of 764 via the Slovin formula. Data were collected through a Likert-scale questionnaire assessing aspects of material, display, audio, and benefits, and analyzed descriptively. The results showed high acceptance (mean: benefits 3.39; material 3.28; display 3.25; audio 3.20; category